Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic

Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Bacillus cellulasensis sp nov., isolated from marine sediment - Mawlankar, Rahul R.; Thorat, Meghana N.; Krishnamurthi, Srinivasan; Dastager, Syed Gulam (Archives of Microbiology, 2016)
A novel bacterial strain NIO-1130(T) was isolated from sediment sample taken from Chorao Island, Goa Province, India, and subjected to a taxonomic investigation. The strain was Gram-positive, aerobic, and motile. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and strain NIO-1130(T) showed highest sequence similarity with Bacillus halosaccharovorans DSM 25387(T) (98.4 %) and Bacillus niabensis CIP 109816(T) (98.1 %), whereas other Bacillus species showed < 97.0 % similarity. Tree based on gyrB gene sequence revealed that strain bacillus group. The major menaquinone was MK-7 and the predominant cellular fatty acids were iso-C-15:0, anteiso-C-15:0, iso-C-17:0, and anteiso-C-17:0. The strain showed a DNA G+C content of 39.9 mol%. DNA-DNA hybridization studies revealed that strain NIO-1130(T) exhibits 70 % similarity with Bacillus halosaccharovorans DSM 25387(T) and Bacillus niabensis CIP 109816T. On the basis of physiological, biochemical, chemotaxonomic and phylogenetic analyses, we consider the isolate to represent a novel species of the genus Bacillus, for which the name Bacillus cellulasensis sp. nov., is proposed. The type strain is NIO-1130(T) (=NCIM 5461(T) = CCTCC AB 2011126(T)).
Keywords: Bacillus sp; Cellulase; Marine sediment; Polyphasic taxonomy